When and how should sepsis patients be fed?. Issue 2 (March 2015) - Elke, Gunnar; Kott, Matthias; Weiler, Norbert
<x xml:space="preserve">Abstract</x> Purpose of review To provide an overview on the recent literature regarding metabolism during sepsis and outcome-related effects of nutrition therapy in septic patients. The question when and how these patients should be fed with respect to macronutrient intake is elaborated. Recent findings Although the incidence of severe sepsis has steadily increased over the past years, still no strong evidence is available with respect to the role of energy and protein provision in these patients. On the basis of recent large randomized trials in mixed patient populations, the updated sepsis guidelines recommend early but limited nutrition via the enteral route rather than targeted feeding. Lately, the results of a large trial challenged the importance of the route of feeding on the clinical outcome of critically ill patients. Four post-hoc analyses of prospective randomized trials including a large number of severely septic patients yielded conflicting results. One reported significant mortality reduction with near-target calorie and protein intake by exclusive enteral nutrition, whereas the second showed an advantage of enteral compared to combined nutrition, albeit resulting in a lower calorie and protein provision. The other two analyses found no association at all of either lower or higher daily caloric or protein intake, respectively, with clinical outcomes. Summary In the absence of strong clinical evidence, pathophysiological findings are discussed and nutritional strategies for septic patients derived. Future studies should explore the individual response to specific exogenous supply of macronutrients and micronutrients in the acute and persistent phase of severe systemic inflammation.